Correlation between laminin-5 immunohistochemistry and human papillomavirus status in squamous cervical carcinoma. Issue 8 (27th July 2007) - Boulet, G A V; Schrauwen, I; Sahebali, S; Horvath, C; Depuydt, C E; Vereecken, A; Broeck, D Vanden; Van Marck, E A; Bogers, J J
Abstract : Background: Human papillomavirus (HPV) plays a critical role in the carcinogenesis of squamous cervical carcinoma. Integration of viral DNA into the host genome is a major contributing factor to malignant transformation. Viral load may influence integration. Aims: To compare HPV status (type, viral load, integration status) between normal samples, carcinoma in situ and invasive carcinoma in order to elucidate the role of HPV in progression to invasive lesions. Methods: The study population comprised 10 biopsy samples from each diagnostic group. Laminin-5 immunohistochemistry was performed to distinguish invasive carcinoma from non-invasive high-grade lesions. Real-time PCR was used to detect specific HPV types, viral load and integrated HPV, with quantification of viral E2 and E6 genes. Results: Invasive carcinomas contained a higher number of laminin-5 immunoreactive cells as compared to non-invasive lesions. Almost all samples contained HPV, with a higher viral load and copy number of HPV16 integrated in E2 in cases of laminin-5 immunoreactivity and cases of invasive carcinoma. High HPV16 viral load was associated with more integrated copies in E2. Conclusions: HPV is important in progression from carcinoma in situ to invasive carcinoma. Viral load and HPV integration influence the development of cervical cancer towards invasiveness. Overall HPV status may be more predictive of patient outcome and may influence patient management.